International trade in health services : a development perspective - Zarrilli, Simonetta ed. (UN GenevaCH, 1998)
Explores a broad range of questions that both developing and industrialized countries may wish to bear in mind as they weigh up the opportunities and drawbacks of fostering trade in health services. Focuses on the development perspective, and contains case studies from countries in the developing world.